Tingkat Kepuasan Konsumen Terhadap Penerapan Bauran Pemasaran Pada UD Olsabara Sukses Sejahtera - Muhamad Yazid Bustomi; Indah Novita Dewi; Rusmiyati Rusmiyati; Wike Pratiwi; Faizal Faizal (JSEP (Journal of Social and Agricultural Economics), 2023)
Consumer satisfaction level of a product could be seen from the performance assessment of the attributes of the marketing mix. The aims of this research were (1) to analyze the level of consumer satisfaction on the marketing mix, (2) to determine priority strategies for increasing customer satisfaction. This research was conducted in December 2021 at UD Olsabara Sukses Sejahtera which was located in the North Sangatta Sub District, Kutai Timur District. The sampling technique used was accidental sampling, namely the sampling by taking visitors of Olsabara who want to be interviewed and to fill out a questionnaire. During the research process, 52 people were willing to be interviewed, so the number of samples was 52 respondents. Data analysis by using the customer satisfaction index (CSI) method, which used to determine the level of consumer satisfaction of the marketing mix at UD Olsabara. Beside that, an important performance analysis (IPA) diagram was used to determine priority strategies for increasing customer satisfaction. The results showed that the level of consumer satisfaction (CSI) was 80.46% which was included in the very satisfied category. The main priority matrix strategy was the attributes which was in quadrant I as the main priority for business owners, namely offline promotion, online promotions, supporting parking facilities, and sales person knowledge of products, and available delivery services.